Police station design and intrusive police encounters: untangling variations in emotions and behaviourally-relevant perceptions across racial groups - St. John, Victor J. (Policing and society, 2023)
Cultivating positive human interactions is at the core of many strategies used to strengthen the relationship between police and community members, with the use of criminal justice architecture being an emergent strategy. This study employs a survey experiment to examine police station design as a strategy to improve police-community relationships and the interactive effect of an individual’s previous encounters with police officers. Study results show that the impact of welcoming police station designs on emotions and behaviourally-relevant perceptions are moderated by intrusive encounters with police officers. Specifically, analyses reveal that people with previous arrest experiences respond more positively when confronted with a welcoming police station design compared to persons without an arrest history. Subgroup analyses further yield variation across Black and White racial groups based on previous encounters with police. Together, the symbol of a welcoming police station may foster more pleasant emotional reactions and behaviourally-relevant perceptions for persons with criminal records, however, it elicits less pleasant emotional reactions and behaviourally-relevant perceptions for persons without a criminal history. Theoretical and practical implications in the pursuit of police architecture that foster positive police-community relationships are discussed.